Nonadiabatic corrections to rovibrational levels of H2 - Pachucki, Krzysztof; Komasa, Jacek (American Institute of Physics, 2009)
The leading nonadiabatic corrections to rovibrational levels of a diatomic molecule are expressed in terms of three functions of internuclear distance: corrections to the adiabatic potential, the effective nuclear mass, and the effective moment of inertia. The resulting radial Schrödinger equation for nuclear motion is solved numerically yielding accurate nonadiabatic energies for all rovibrational levels of the H2 molecule. Results for states with J ≤ 10 are in excellent agreement with previous calculations by Wolniewicz, and for states with J>10 are new.
Keywords: Nonadiabatic corrections; Rovibrational levels; Effective nuclear mass; Radial Schrödinger equation; Hydrogen molecule; Correlated Gaussian functions